Advantages and disadvantages of using artificial intelligence (AI) in architectural applications (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Nowadays, the position of artificial intelligence is increasing all over the world. Almost Anotation: nowadays, the position of artificial intelligence is increasing all over the world. In almost every area we can see his intervention. This gives us a certain relief. Saving our time, for example, wants to know, allows us to find exactly and quickly the information we want to learn. In certain areas it can even do different things without human intervention. The main content of the article is such in the applications used in the field of architectand we can see its intervention in one field. This gives us a certain relief. Saving our time, for example, wants to know, allows us to find exactly and quickly the information we want to learn. In certain areas it can even do different things without human intervention. The main content of the article is to consider the good and bad aspects of artificial intelligence in the applications used in the field of architecture.